Niall Brennan and David Gudelunas, Rupaul's Drag Race and the Shifting Visibility of Drag Culture - Armando Ferrara (Università degli Studi di Torino, 2019)
Niall Brennan and David Gudelunas, Rupaul's Drag Race and the Shifting Visibility of Drag Culture (Book Review)